2014
DOI: 10.1002/jctb.4530
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced saccharification of lignocellulosic biomass by pretreatment with quaternary ammonium hydroxide

Abstract: BACKGROUND As one of the most abundant natural resources, lignocellulosic biomass is usually utilized at low efficiencies because of its complicated structure and poor degradability, and pretreatments prior to utilization are therefore considered necessary. To overcome the disadvantages of traditional pretreatments for lignocellulosic biomass, a method based on the application of quaternary ammonium hydroxide was investigated. RESULTS Remarkable structural transformation and compositional changes were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…23 Another study reported 4-12 hours of predicted time of incubation by using response surface methodology using cellulases enzymes. 24 Similarly, enzyme concentration considerably effect the hydrolytic potential of b-xylosidase and maximum saccharification percentage (13.5%) was obtained after addition of 30 units of recombinant b-xylosidase in reaction mixture containing sugarcane bagass while 10% and 10.5% saccharification was observed with both rice straw and wheat straw when same amount of enzyme was used (Fig. 2D).…”
mentioning
confidence: 79%
“…23 Another study reported 4-12 hours of predicted time of incubation by using response surface methodology using cellulases enzymes. 24 Similarly, enzyme concentration considerably effect the hydrolytic potential of b-xylosidase and maximum saccharification percentage (13.5%) was obtained after addition of 30 units of recombinant b-xylosidase in reaction mixture containing sugarcane bagass while 10% and 10.5% saccharification was observed with both rice straw and wheat straw when same amount of enzyme was used (Fig. 2D).…”
mentioning
confidence: 79%
“…12 Lignocellulosics cannot be saccharified by cellulases to yield sugar unless they are processed through mechanical, physical, and chemical pre-treatments to remove the inhibitory lignin complex, to reduce the crystallinity and degree of polymerization of cellulose, to increase the surface area available for the enzymes, and to enhance the susceptibility of the substrates to enzymes. 13 , 14 , 15 , 16 Lactic acid is a valuable organic acid due to its broad applications in pharmaceutical, leather, and food industries, and its potential for the production of biodegradable poly-lactic acid—an environmentally friendly alternative to plastic. 17 , 18 , 19 In this study, an optimized production of glucose syrup by enzymatic saccharification of treated and untreated date palm wastes was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to, it has been reported that the higher microbial cellulase productivity is dependent upon the pretreatment of substrates compared with non-pretreated ones. These pretreatments would be acid and/or alkali, organic solvents, or steam explosion (Carrasco et al 1994;Mahmoud et al 2021;Zhong et al 2015). Compared with different pretreatments, bacterial cultures were considered as an efficient pretreatment strategy without any chemical's consumption or dramatic physical circumstances (such as high temperature, and high pressure) (Amarasekara and Shanbhag 2013).…”
Section: Discussionmentioning
confidence: 99%